THE RESEARCH OF THE OPERATION MODES OF THE DIESEL LOCOMOTIVE CHME3 ON THE IMITATION MODEL - S. G. Buriakovskyi (National Technical University "Kharkiv Polytechnic Institute", 2018)
Introduction. Fuel consumption by diesel locomotive during operation depends significantly on many factors, among which the main is the mode of driving a train. Purpose. Research on the mathematical model of the modes of driving a train on the site of Kharkiv-Merefa with the purpose of the main oscillograms of the operation of the locomotive on the site. Methodology. A mathematical model of the operation of the main units of the locomotive CHME3 in the Matlab environment was developed. The model of the diesel engine is based on the calculated indicator diagram of its operation, which is approximated by a continuous dependence. The control panel operates on a system of conditions, the purpose of which is to maintain the set speed. Results. In the course of the simulation, statistical data were obtained on the fuel consumption of the diesel locomotive when it operated on a section with a train of constant mass. Based on the data obtained, a three-dimensional surface is constructed showing the dependence of the fuel consumption on the time of the site's exploration and the maximum speed on the site. Practical value. The dependence obtained can be used to optimize the driving behavior of trains along a section. The apparent dependence of fuel consumption on the driver's behavior is the basis for the further development of automatic locomotive speed control systems.